The role of Russia in the world education market - Fisenko, Olga (2021)
This article considers the features of the education market formation. It is shown that the undoubted leaders by number of foreigners involved in educational projects are Western European countries (Germany, France, Great Britain) and North American countries (USA and Canada).  Currently, the world education market reflects the patterns of interaction between producers, providers and users of educational services. The current education system is aimed at meeting the demand of foreign citizens on educational services through the use of a whole set of technologies related to improving skills and competitiveness of labor market specialists. It is proved that the leading market is associated with attracting foreign students to obtain higher education in Russia. In this article the main trends in the development of Russian education system were analyzed and results of the "Export of Education" program were described.